Evaluation of heavy crude oils processing with enhanced heat recovery to overcome current limitations (2014)
There are two distillation units at the BAYERNOIL facility in Vohburg Germany -- One of them processes only light crude oils whereas the other both light and heavy crude oils -- The processing capacity of the second is limited by the heater duty which during the last three years and by processing heavy crude oils has often reached the maximal allowed duty -- The main subject of this thesis is to evaluate the effect of an enhanced heat recovery capacity, available in the unit that processes only light crude oils by processing heavy crude oils and to determine where or not, the changeover of the distillation units operational mode is a viable option to overcome the current processing capacity limitation -- Processing heavy crude oils in the unit with the enhanced heat recovery achieved an effective decrease on the heater duty of the crude distillation unit -- However, the thermal dependency between the crude and the vacuum distillation units, caused an increase in the vacuum unit heater duty and a reduction in the steam generation -- This showed that no energetic benefit is accomplished by changing the units operational modes, but rather a shift of the energy requirements in the studied system -- Nevertheless, this energy shift reduces in the first instance the heater duty of the crude distillation unit, presenting an option to overcome the current processing capacity limitation by processing heavy crude oils -- Processing heavy crude oils in the unit with the enhanced heat recovery, implies the permanent processing of light crude oils in the other unit -- This generates heat losses by the final cool down of the atmospheric residue before it is taken to the storage tanks and presents an argument against a simple changeover of the distillation units operational mode